A Long Window Event Study of Financial Performance: Does Debt Restructuring Triumph Over Bankruptcy? - Irene Angelina; Gabiella Lavenia Sutjiono; Irene Citrawati; Nanik Linawati (Master of Accounting Universitas Trunojoyo Madura, 2024)
The number of companies undergoing debt restructuring in Indonesia has significantly increased yearly. Debt restructuring, as an alternative to mergers and acquisitions, has become a strategy for many companies facing financial challenges. This research aims to conduct a long-window event study of debt restructuring in Indonesian companies from 2003 – 2022. This study utilizes a method involving the differential analysis of financial performance ratios of companies two years before and after undertaking debt restructuring. The main financial ratios focused on in this research are liquidity ratio, solvency ratio, profitability ratio, and efficiency ratio. This study involves 44 samples and is analyzed through paired sample t-tests using SPSS statistical analysis. Based on the empirical findings, this research concludes that debt restructuring has caused significant differences in the cash ratio, profit margin, return to asset, and asset turnover. This study helps investors and creditors to identify signs of betterment of companies undertaking debt restructuring via financial ratios.